2021
DOI: 10.1002/humu.24292
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel deep intronic PAH gene variants in patients diagnosed with phenylketonuria

Abstract: Phenylketonuria (PKU) is caused by phenylalanine hydroxylase (PAH) gene variants. Previously, 94.21% of variants were identified using Sanger sequencing and multiplex ligation‐dependent probe amplification. To investigate the remaining variants, we performed whole‐genome sequencing for four patients with PKU and unknown genotypes to identify deep intronic or structural variants. We identified three novel heterozygous variants (c.706+368T>C, c.1065+241C>A, and c.1199+502A>T) in a deep PAH gene intron. We detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…We found that nearly 90% of patients with previously undefined genotypes carried deep intron variants. Three deep intronic variants c.1199 + 502A > T, c.1065 + 241C > A and c.707-59C > G detected in our study were also reported in other variant spectrum studies of Chinese PKU patients [ 16 , 17 ]. Our study provided additional patient data to support findings related to these three variants by sequencing a larger population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that nearly 90% of patients with previously undefined genotypes carried deep intron variants. Three deep intronic variants c.1199 + 502A > T, c.1065 + 241C > A and c.707-59C > G detected in our study were also reported in other variant spectrum studies of Chinese PKU patients [ 16 , 17 ]. Our study provided additional patient data to support findings related to these three variants by sequencing a larger population.…”
Section: Discussionsupporting
confidence: 89%
“…The splicing initiation of premRNA needs to be recognized by spliceosome and splice site (ss) sequences: the 5′ss (donor site), the 3′ss (acceptor site), and the branching point [ 26 , 27 ]. Jin et al [ 17 ] reported that the c.1199 + 502A > T variant of PAH acted to strengthen a cryptic branching point, and minigene expression showed that pseudoexon retention appeared in intron 11. The mechanism of pseudoexon inclusion caused by deep intronic variants may be due to activation of noncanonical splice sites, alterations to the splicing regulatory environment or loss of splice site competition [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variants might involve large insertion/deletions, deep intronic variants or those located in the 5’ and 3’ untranslated regions. This was further demonstrated by a recent study that rare and recurrent variants located deep within PAH introns were not uncommon in phenylketonuria patients in China [ 18 ]. A concern should be raised that some variants located in exons detected in IEMs patients, especially those with high allele frequencies in population databases, might cover up the true disease-causing variants mentioned above.…”
Section: Discussionmentioning
confidence: 75%
“…These findings support previously described genotype-phenotype correlation, suggesting that BH4 responsiveness may be anticipated by certain PAH phenotypes. Molecular testing may also fail to identify individuals with PKU who have pathogenic variants that are not detected by the standard sequencing method such as deep intronic mutations [ 33 , 34 ]. As seen in our study, a second mutation was not detected in one patient.…”
Section: Discussionmentioning
confidence: 99%